Past, Present, and Future of Corporate Social Responsibility and Earnings Management Research - Fatimah Noor Rashidah, Mohd Sofian; Mohd Sabrun, Ibrahim; Rusnah, Muhamad (AABFJ, 2022)
For decades, corporate social responsibility (CSR) has been an area at the heart of business research. The aspects of CSR that researchers have been focusing on have grown exponentially. Most research efforts have dwelled on its positive effects, including good behavioural changes, promising financial performance, social investment and development, and environmental preservation and protection. On the other hand, several scholars have questioned the credibility of CSR and its link to unethical financial conduct, particularly earnings management. This review paper uses a systematic literature review to conduct bibliometric analysis, content analysis, and thematic analysis in order to identify trends and outcomes of CSR reporting and earnings management research. The literature review search is guided by PRISMA and analyses 152 Scopus-indexed articles between 2005 and 2021. As a result, this paper reveals the most influential authors and articles, leading journals and countries, and research cluster networks. This review also outlines the theoretical perspectives and future direction of CSR and earnings management research. In addition, this review paper provides critical and beneficial insights for stakeholders and researchers.